Ética o Conócete a ti mismo. - VALDEZ, VICTORIA L. (Revista Española de Filosofía Medieval, 2024)
The article in the Spanish Journal of Medieval Philosophy focuses on the work "Ethics or Know Yourself" by Peter Abelard, translated by Natalia Jakubecki. The work addresses morality and sin in the Middle Ages, presenting a new structured theory on the subject. Jakubecki's Spanish translation is the first based on the critical edition by Raigner Ilgner, adding unpublished passages and maintaining fidelity to the original Latin. The work highlights the importance of self-knowledge and the relationship with God in Abelard's doctrine, making it a relevant read for those studying medieval philosophy.